Amish Greenhouse : The Robin's Greeting - Book 3 - Brunstetter, Wanda E. (Uhrichsville, OH : Shiloh Run Press, an imprint of Barbour Publishing, Inc., 2021)
"For the past two years Belinda King, along with her two grown daughters and teenage son, has been struggling to keep the family greenhouse running. Despite disconcerting events that have threatened to put them out of business, they have survived two growing seasons. And now Belinda can focus on the two suitors vying for her attention. Herschel Fisher, a new acquaintance, makes her feel relaxed, and Monroe Esh, an admirer from her past, reminds her of her youth. But just when Belinda thinks she can choose between her suitors, life throws more trials her way"--Back cover.
Keywords: Amish -- Fiction; Greenhouses -- Fiction; Man-woman relationships -- Fiction; Single mothers -- Fiction; Widows -- Fiction; Pennsylvania -- Fiction; Christian fiction; Detective and mystery fiction; Religious fiction; Romance fiction